Reducing saturated fat intake lowers LDL-C but increases Lp(a) levels in African Americans: the GET-READI feeding trial - Hayley G. Law; Muhammad A. Khan; Wei Zhang; Heejung Bang; Jennifer Rood; Marlene Most; Michael Lefevre; Lars Berglund; Byambaa Enkhmaa (Journal of Lipid Research, 2023)
Reducing dietary saturated fatty acids (SFA) intake results in a clinically significant lowering of low-density lipoprotein cholesterol (LDL-C) across ethnicities. In contrast, dietary SFA’s role in modulating emerging cardiovascular risk factors in different ethnicities remains poorly understood. Elevated levels of lipoprotein(a) [Lp(a)], an independent cardiovascular risk factor, disproportionally affect individuals of African descent. Here, we assessed the responses in Lp(a) levels to dietary SFA reduction in 166 African Americans enrolled in GET-READI (The Gene-Environment Trial on Response in African Americans to Dietary Intervention), a randomized controlled feeding trial. Participants were fed two diets in random order for 5 weeks each: 1) an average American diet (AAD) (37% total fat: 16% SFA), and 2) a diet similar to the Dietary Approaches to Stop Hypertension (DASH) diet (25% total fat: 6% SFA). The participants’ mean age was 35 years, 70% were women, the mean BMI was 28 kg/m2, and the mean LDL-C was 116 mg/dl. Compared to the AAD diet, LDL-C was reduced by the DASH-type diet (mean change: −12 mg/dl) as were total cholesterol (−16 mg/dl), HDL-C (−5 mg/dl), apoA-1 (−9 mg/dl) and apoB-100 (−5 mg/dl) (all P < 0.0001). In contrast, Lp(a) levels increased following the DASH-type diet compared with AAD (median: 58 vs. 44 mg/dl, P < 0.0001). In conclusion, in a large cohort of African Americans, reductions in SFA intake significantly increased Lp(a) levels while reducing LDL-C. Future studies are warranted to elucidate the mechanism(s) underlying the SFA reduction-induced increase in Lp(a) levels and its role in cardiovascular risk across populations.